Cardiovascular Effects of Caffeic Acid and Its Derivatives: A Comprehensive Review - Silva, Henrique; Lopes, Nuno Miguel F. (Frontiers in Physiology, 2020)
Caffeic acid (CA) and its phenethyl ester (CAPE) are naturally-occurring hydroxycinnamic acids with an interesting array of biological activities; e.g. antioxidant, anti-inflammatory, antimicrobial and cytostatic. More recently, several synthetic analogs have also shown similar properties, and some with the advantage of added stability. The actions of these compounds on the cardiovascular system have not been thoroughly explored despite presenting an interesting potential. Indeed the mechanisms underlying the vascular effects of these compounds particularly need clarifying. The aim of this paper is to provide a comprehensive and up-to-date review on current knowledge about CA and its derivatives in the cardiovascular system. Caffeic acid, CAPE and the synthetic caffeic acid phenethyl amide (CAPA) exhibit vasorelaxant activity by acting on the endothelial and vascular smooth muscle cells. Vasorelaxant mechanisms include the increased endothelial NO secretion, modification of calcium and potassium channels, and modulation of adrenergic receptors. Together with a negative chronotropic effect, vasorelaxant action contributes to lower blood pressure, as several preclinical studies show. Their antioxidant, anti-inflammatory and anti-angiogenic properties contribute to an important anti-atherosclerotic effect, and protect tissues against ischemia-reperfusion injuries and the cellular dysfunction caused by different physico-chemical agents. There is an obvious shortage of in vivo studies to further explore these compounds’ potential in vascular physiology. Nevertheless, their favorable pharmacokinetic profile and overall lack of toxicity make these compounds suitable for clinical studies.